An integrated agriculture and nutrition program in Burkina Faso has positive intrahousehold spillover effects on maternal and child nutritional status, but no sustained longterm improvements in household welfare - Bliznashka, Lilia; Olney, Deanna K.; Ruel, Marie T.; Rawat, Rahul; Becquey, Elodie; Birba, Ousmane (Wiley, 2016)
Integrated agriculture and nutrition programs have been shown to increase production and consumption of micronutrient-rich foods. However, current evidence about their effectiveness in improving maternal and child nutritional status is limited. Recent results from a cluster-randomized controlled trial (RCT) of Hellen Keller International’s (HKI) enhanced homestead food production (EHFP) program in Burkina Faso showed significant positive impacts both on agricultural production and on reducing the prevalence of diarrhea, wasting and anemia among children and of underweight among their mothers over the 2 y program period (2010–2012). Yet, little is known about the sustainability and intra-household spillover of impacts on household, maternal and child outcomes from this and similar types of programs.